Opportunity to learn in Norwegian and Finnish lower secondary mathematics textbooks - Haavold, Per Øystein; Storaas, Ane; Johnsen, Marthe; Strand, Kristoffer; Heimstad, Carina (NOMAD Nordic Studies in Mathematics Education, 2025)
Although both Finland and Norway are part of a common Nordic education culture, Finland have consistently outperformed the other Nordic countries in PISA studies. In this study, we compare Finnish and Norwegian textbook series. The results indicate that both textbook series largely facilitate skill efficiency, and most tasks are low cognitive demand. However, the Finnish textbook series facilitate conceptual understanding to a greater degree. The Finnish textbook series also introduce and develop connections between a greater number of mathematical ideas, and there is a greater number and proportion of high cognitive demand tasks in the Finnish textbooks.